2015
DOI: 10.1021/acs.est.5b02042
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulation by Glycerol Phosphate to Precipitate Recalcitrant Uranium(IV) Phosphate

Abstract: Stimulating the microbial reduction of aqueous uranium(VI) to insoluble U(IV) via electron donor addition has been proposed as a strategy to remediate uranium-contaminated groundwater in situ. However, concerns have been raised regarding the longevity of microbially precipitated U(IV) in the subsurface, particularly given that it may become remobilized if the conditions change to become oxidizing. An alternative mechanism is to stimulate the precipitation of poorly soluble uranium phosphates via the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 52 publications
(107 reference statements)
9
78
0
Order By: Relevance
“…Understanding the speciation, mechanism, and kinetics of U transformation under various conditions relevant to natural and engineered systems is essential to predicting and controlling the migration of U in contaminated environments. Recently, bioreduction accompanied by the phosphate-precipitated U(VI) phase has been considered as a potential pathway for U transformation to U(IV)-phosphate mineral phases that could further limit U mobility [12,14]. Previous studies have shown that such processes can compete with or limit uraninite formation during the bioreduction of aqueous U(VI) in the presence of dissolved phosphates [54].…”
Section: Implication Of U(iv)nps Reactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the speciation, mechanism, and kinetics of U transformation under various conditions relevant to natural and engineered systems is essential to predicting and controlling the migration of U in contaminated environments. Recently, bioreduction accompanied by the phosphate-precipitated U(VI) phase has been considered as a potential pathway for U transformation to U(IV)-phosphate mineral phases that could further limit U mobility [12,14]. Previous studies have shown that such processes can compete with or limit uraninite formation during the bioreduction of aqueous U(VI) in the presence of dissolved phosphates [54].…”
Section: Implication Of U(iv)nps Reactivitymentioning
confidence: 99%
“…Murray et al observed that U can be strongly adsorbed on apatite, which has a high capacity for retaining U by phosphate mineralization [7]. Biotic approaches for immobilizing subsurface U were also examined using microbial phosphatase activities that promote the in situ sequestration of U as an insoluble phosphate mineral [11,12]. In the presence of organophosphates under reducing conditions, the biomineralization of U(VI)-phosphate minerals has been shown to be more effective for removing U than bioreduction to U(IV) species; e.g., uraninite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulating a sediment microbial community with G2P under anaerobic conditions led to the formation of crystalline U(IV) phosphate minerals (e.g. ningyoite), which were more recalcitrant to oxidative remobilization than the products of microbial U(VI) reduction (Newsome et al, 2015b). An isolated strain (Serratia sp.)…”
Section: Mechanisms and Microbesmentioning
confidence: 99%
“…Recently, various methods that use biomineralization by microorganisms to remove radionuclides from contaminated solutions have been studied (6)(7)(8). Using biogenic minerals, dispersed radionuclides at low concentrations can be removed for a long period at a low cost.…”
mentioning
confidence: 99%